Pengembangan Media Pembelajaran Ular Tangga Pada Mata Pelajaran Matematika Materi Pecahan Campuran Di Kelas VB SDN PANCORAN 07 PAGI JAKARTA - Fitri Noviana; Satriyani, Febrianti Yuli (Jurnal Pendidikan Dasar, 2025)
The research method used is the research and development method (Research and Development) which refers to the formulation of Dick and Carey with stages: 1) Identifying instructional needs and writing general instructional objectives 2) Instructional analysis 3) Identifying behavior and initial learner characteristics 4) Writing specific instructional objectives5) Developing learning outcomes assessment tools 6) Developing instructional strategies 7) Develop instructional materials 8) Design and carry out formative evaluation 9) Instructional System 10) Implementation of Summative Evaluation and Diffusion of Innovation. character is carried out by distributing questionnaires to expert validators and respondents. The results obtained from the design expert get a percentage of 82% "Good and feasible", the results obtained from the material expert get a percentage of 91% "Good and feasible". In the small-scale trial, the percentage was 66%, while in the field trial, the presentation increased to 88%.